The Quality and Efficiency Between Public and Private Firms: Evidence from Ambulance Services - Daniel Knutsson; Björn Tyrefors (Research Institute of Industrial Economics (IFN), 2020)
Economic theory predicts that outsourcing public services to private firms will reduce costs, but the effect on quality is ambiguous. We explore quality differences between publicly and privately owned ambulances in a setting where patients are as good as randomly assigned to ambulances with different ownership statuses. We find that privately owned ambulances perform better in response to contracted quality measures but perform worse in response to noncontracted measures such as mortality. In fact, a randomly allocated patient has a 1.4% higher risk of death within 3 years if a private ambulance is dispatched (in aggregate, 420 more deaths each year). We also present evidence of the mechanism at work, suggesting that private firms cut costs at the expense of ambulance staff quality.
Keywords: D22; D44; H44; I11; L33; P48; 330; Public outsourcing; Pre-hospital care; Healthcare quality; Health